2021
DOI: 10.1002/adsc.202100301
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Additional Capability from in Water Reaction Conditions: Aldol versus Knoevenagel Chemoselectivity

Abstract: Aldol reaction chemoselectivity, racemic or enantioselective, has not been previously demonstrated in the presence of Knoevenagel active functional groups. Here, we show that unhindered β-diketones remain unreacted while a ketone moiety undergoes a highly enantioselective aldol desymmetrization resulting in three new stereogenic centers using in water reaction conditions. A mechanistic hypothesis for the chemoselective formation of either aldol or Knoevenagel products is presented. It elucidates how these amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“… [48c,68,69] In a similar vein of research, it was recently shown that triketones consisting of a cyclohexanone carbonyl moiety and an unhindered β‐diketone, can chemoselectively undergo an aldol reaction (Scheme 8). [21] This is the first example of aldol reactivity superseding Knoevenagel reactivity.…”
Section: Regioselective Mono‐aldol Reactions Of Di‐ or Higher‐ketonesmentioning
confidence: 87%
See 4 more Smart Citations
“… [48c,68,69] In a similar vein of research, it was recently shown that triketones consisting of a cyclohexanone carbonyl moiety and an unhindered β‐diketone, can chemoselectively undergo an aldol reaction (Scheme 8). [21] This is the first example of aldol reactivity superseding Knoevenagel reactivity.…”
Section: Regioselective Mono‐aldol Reactions Of Di‐ or Higher‐ketonesmentioning
confidence: 87%
“…Low yield generally implies the limiting reagent has not been fully consumed, i. e ., by‐product formation is uncommon. In theory this can be solved by increasing the catalyst loading, but our observations have shown that a catalyst loading plateau is commonly reached [21,48] . For example, repetition of an optimized reaction, in which the limiting substrate is only 85 % consumed, with, e. g ., double or even quadruple the catalyst loading, often provides only incremental increases in yield (<5%).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations